2015
DOI: 10.1016/j.physletb.2015.02.047
|View full text |Cite
|
Sign up to set email alerts
|

On M-theory fourfold vacua with higher curvature terms

Abstract: We study solutions to the eleven-dimensional supergravity action, including terms quartic and cubic in the Riemann curvature, that admit an eight-dimensional compact space. The internal background is found to be a conformally Kahler manifold with vanishing first Chern class. The metric solution, however, is non-Ricci-flat even when allowing for a conformal rescaling including the warp factor. This deviation is due to the possible non-harmonicity of the third Chern-form in the leading order Ricci-flat metric. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 33 publications
4
64
0
2
Order By: Relevance
“…More precisely this means that to any finite order in l P the metric of the fourfold can be corrected so that N = 2 supersymmetry is preserved to that order. This has recently been partially verified in [5] where it was shown that the metric gets corrected at order l 6 P away from the Ricci-flat CY metric while still retaining its Kähler property.…”
Section: Jhep09(2015)107mentioning
confidence: 76%
See 2 more Smart Citations
“…More precisely this means that to any finite order in l P the metric of the fourfold can be corrected so that N = 2 supersymmetry is preserved to that order. This has recently been partially verified in [5] where it was shown that the metric gets corrected at order l 6 P away from the Ricci-flat CY metric while still retaining its Kähler property.…”
Section: Jhep09(2015)107mentioning
confidence: 76%
“…The expansions for the light modes will generally get modified at order l 6 P , where the fourfold geometry gets corrected away from Ricci-flatness [5,12]. However these modifications are subleading, as far as the mass spectrum of the light modes is concerned, and will not be necessary for our analysis.…”
Section: Jhep09(2015)107mentioning
confidence: 98%
See 1 more Smart Citation
“…However, a complete discussion of the reduction results of the R 4 -sector on a Calabi-Yau threefold involves a proper treatment of the ten-dimensional background solution at this order, with a successive dimensional reduction on this modified background. The analog scenario of the R 4 -sector in a dimensional reduction on a CalabiYau fourfold with Kähler deformations was discussed in the context of M-theory/F-theory in [34][35][36][37][38], where a complete treatment involving the corrected background was provided. Furthermore, the dimensional reduction of the R 4 -sector was discussed in related set-ups in [39,40].…”
Section: Jhep04(2017)063mentioning
confidence: 99%
“…Of course, this problem is well-known to experts on the field, but unfortunately, as long as the elevendimensional Supergravity l P -corrected Killing spinor equation is not known, it seems not possible to solve it in a completely rigorous way. Important steps in this direction have been made in references [45][46][47], where a thoroughly and consistent analysis of M-theory compactifications in the presence of l P -corrections has been made, and even an educated guess for the l P -corrected Killing spinor equation has been proposed. Remarkably enough, the integrability condition of the l P -corrected proposal for the Killing spinor equation is compatible with the l P -corrected equations of motion, which definitely suggests that if the educated guess is not already the correct l P -corrected Killing spinor equation, it cannot be far from being it.…”
Section: Jhep09(2015)178mentioning
confidence: 99%